Hacked kestrels (Falco tinnunculus) show similar patterns of post-fledging food dependency as wild reared birds: implications for best practice in release management of orphaned raptors - Thavarajah, Nathan; Fenkes, Miriam (Wildlife Rehabilitation Bulletin, 2022)
<span style="color: #000000; font-family: -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen, Ubuntu, Cantarell, 'Fira Sans', 'Droid Sans', 'Helvetica Neue', sans-serif; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">One of the challenges of wildlife rehabilitation is ensuring that rehabilitated animals have the required characteristics for survival after release. This is especially the case for orphaned animals that normally develop survival skills during a prolonged period of parental care. For raptors, this is called the post-fledging dependency period (PDP), where parents provide nutritional support to juveniles whilst they develop the physiological and behavioural characteristics required to successfully hunt prey. Orphaned raptors can be rehabilitated and released using a method termed “hacking,” a type of “soft-release” where fledglings are released from a nest box, which they learn to associate with food. This method gives the birds an opportunity to develop prey capture skills, whilst continued nutritional support is provided by rehabilitators at the box. Here, we used a hacking method to rehabilitate and release 15 orphaned kestrels (<em style="color: #000000; font-family: -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen, Ubuntu, Cantarell, 'Fira Sans', 'Droid Sans', 'Helvetica Neue', sans-serif; font-size: medium; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Falco tinnunculus) and observed the pattern of return to the hacking box. Of the released birds, 80% returned to the hack site for food at least once. The average number of days birds returned to the box was 12.67 ± 8.76, and there was a clear trend towards a gradual decrease in return rate (number of visits to the box per day) over time. Our observations are comparable to patterns of PDP in wild-reared kestrels and we therefore suggest that orphaned kestrels can be successfully rehabilitated in this way.